CWLD.ID: INOVASI DIGITAL ORIGINAL SEBAGAI SISTEM AGGREGATOR PRODUK WAKAF UANG UNTUK MENINGKATKAN LITERASI DAN AKSESIBILITAS WAKIF - Doni Maradona; Saiful Anwar (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study objectives to develop and analyse CWLD.ID, a digital platform that functions as an aggregator for Cash Waqf Linked Deposit (CWLD) products from various Islamic financial institutions (LKS-PWU). The research is encouraged by the low level of waqf literacy in Indonesia and the lack of integrated digital access to CWLD product information. The study employs a Design and Development Research (DDR) approach to design a prototype of CWLD.id, followed by a SWOT analysis to assess the platform's strengths, weaknesses, opportunities, and threats. CWLD.id includes features such as a CWLD product marketplace, Islamic waqf education, return simulations, and transparent reporting on fund usage and institutional legitimacy. The findings indicate that CWLD.id has significant potential to improve public literacy on cash waqf and facilitate easier access for wakif to choose products aligned with Islamic principles and social impact. This study also affirms that CWLD.id is an original digital innovation personally designed by the researcher as a practical solution in the cash waqf ecosystem in the digital era.